Multiple Routes to Manufacturing SME Performance in DKI Jakarta: An fsQCA Study of Entrepreneurial Orientation, Normative Pressure, and Dynamic Capabilities - Darwin Raja Unggul Saragih; Wahyuningsih Santosa; Bahtiar Usman; Andri Dayarana K. Silalahi (Yayasan Sinergi Kawula Muda, 2026)
This study explains why manufacturing SMEs in DKI Jakarta, Indonesia, achieve different performance outcomes under similar external conditions. Drawing on dynamic capability theory, it examines entrepreneurial orientation, normative pressure, and dynamic capabilities as interdependent configurations rather than isolated linear predictors. Using 314 calibrated SME responses, fuzzy-set qualitative comparative analysis evaluates five conditions: innovativeness, proactiveness, normative pressure, sensing capability, and reconfiguration capability. The results identify two robust pathways to positive performance, with overall solution coverage of 0.870 and consistency of 0.961, and two exploratory pathways to negative performance, with coverage of 0.835 and consistency of 0.767. Strong performance arises through a normatively supported proactive-sensing pathway and an entrepreneurial-capability pathway combining innovativeness, proactiveness, sensing, and reconfiguration. Weak performance occurs when firms sense external expectations but lack innovativeness and reconfiguration capability, or when all five conditions are absent. These negative configurations require caution because their consistency and PRI support are weaker. The findings show that sensing capability alone does not ensure superior performance; its contribution depends on alignment with entrepreneurial and reconfiguration capacities. The study advances SME performance research by demonstrating that configurational interdependencies explain outcomes more effectively than separate antecedents. It also reveals causal asymmetry between pathways producing strong and weak performance.